PERANCANGAN TRANSPARENT PROXY SERVER CLEAROS DI JARINGAN HOTSPOT INSTITUT TEKNOLOGI PADANG - Indra Warman; Rahmat Hidayat (Jurnal Momentum ISSN 1693-752X)
Internet technology has become an important part in many areas of life. Internet technology allowing users to get the latest information from around the world. For an institution or company that wants to have a internet connection, it must lease bandwidth to ISP’s that serve the internet services. But, the price of bandwidth is quite expensive, so not all people can use the internet with convenient.Aim of this research building a proxy server in order to overcome the problem of bandwidth availability. This research was an experimental about proxy server, using ClearOS operating system. The proxy applications that used is lusca squid 14942 version. Squidanalyzer is used to see the performance statistics of the proxy server.In this research, the proxy is able to save on bandwidth usage, and increase the speed of internet connections at Padang Institute of Technology hotspot network reach 10 to 30 times faster. In this research, not all objects on the internet can be cached by proxy. Keywords : Internet, Proxy, ClearOS, Squid, Lusca